Варіабельність поселенських структур давньоруського часу у літописному Пороссі - Борисов, А.В. (Археологія і давня історія України, 2020)
У статті представлені попередні результати аналізу бази даних поселенських археологічних пам’яток та реконструйованих населених пунктів давньоруського часу на території літописного Поросся. Здійснено аналіз розмірів населених пунктів давнини. The preliminary results of the analysis of present database of settlement sites and reconstructed settlements in the territory of the Ros river basin (annalistic Porossya) are considered in the paper. The size and structure of the settlements are analyzed. This paper uses information on the area of distribution of the cultural layer recorded by researchers in the form of literary and graphic descriptions of the sites. Data on the size of settlements of Medieval Porossya region were collected in the thematic geo-information system «Porossya-01».